Sustainable Development in English Language Teaching: Prevailing Trends, Challenges, and Outcomes - Azizah, Nurul Latifatul; Ali Mustofa; Pratiwi Retnaningdyah (Universitas Nahdatul Ulama Surabaya, 2025)
The current trends, challenges, and outcomes of integrating the Sustainable Development Goals into English Language Teaching (ELT) are examined in this review. This study employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) technique and systematically reviewed 25 research articles identified through a targeted search with keywords such as